Teaching how to critically read Indo-Caribbean bodies in nineteenth-century postcards - Rupa Pillai (Journal of Indentureship and its Legacies)
Starting in 2017, the Kislak Center at the University of Pennsylvania has collected postcards dating from the late nineteenth century that depict Indo-Caribbean life and culture in Trinidad, British Guiana, Suriname and Jamaica. From village scenes to Indo-Caribbean women in studio portraits, the bodies featured in these postcards appear in ethnographic views to promote perceptions of Indo-Caribbeans as being exotic and different. However, as I demonstrate, these postcards are valuable pedagogical tools to help students appreciate how race is constructed visually across locations and time. Drawing upon my use of this postcard collection in the past six years in my course on ‘The Asian Caribbean’, I will discuss how I prepare students to critically read Indo-Caribbean bodies featured in these postcards. From learning the history of indenture in the Caribbean to looking at similar colonial representations from the South Asian subcontinent, the students better appreciate how colonial ideologies of race, gender and progress are produced and reinforced through the visual.